Inovatif Rangkaian Bunga Tangan untuk Pengantin Barat - Nurulisma Saputri; Alfida Khoirunnisa (Garina, 2025)
The bridal hand bouquet in Western weddings is an important element symbolizing the sanctity of the marriage. The hand bouquet serves as an accessory that complements the appearance of the bride and portrays her as the queen on her special day. This study aims to explain the innovative process of arranging Hologram Flower Bouquets, Rattan Flower Bouquets, and Coconut Flower Bouquets, as well as to validate the product of the book "Creations of Bouquets for Brides". The methodology used includes observation, literature review, documentation, and questionnaires. The process of arranging the Hologram Flower Bouquet, Rattan Flower Bouquet, and Coconut Flower Bouquet consists of three stages: preparation of tools, materials, and steps for arranging the flowers. The validation results from three expert validators for the book "Bridal Hand Bouquets" show the following scores: 12 (good) for the material indicator matching the title, 11 (good) for the images, 11 (good) for completeness of content, 12 (good) for layout, 11 (good) for image clarity, 11 (good) for appearance, 10 (fair) for information clarity, 9 (fair) for sentence accuracy, and 9 (fair) for formal or informal language. It is recommended to create bouquets using artificial or dried flowers and to incorporate unique accessories.